Manure management decision-making of cattle-feed growers in northeastern Colorado - Stroheim, Erich, author; Carolan, Michael S., advisor; Lacy, Michael G., advisor; Hogan, Michael J., committee member; Hoag, Dana L. K., committee member (Colorado State University. Libraries, 2023)
Rural water supplies, including household wells and small-town water systems, located near livestock production and irrigated agriculture operations are often at risk for high nitrate-levels resulting from concentrated feedlot manure disposal as administered by livestock-feed farmers. Efficient manure management is one approach to minimizing nutrient pollution of rural groundwater and surface waters, and crop-farmers near the feedlots are de facto manure managers. This study observes how farmers value manure and whether they frame manure as a waste disposal issue, as an important fertilizer resource, or both. This distinction places manure management in the overlap between environmental sociology and natural resource sociology. The study identifies factors related to how farmers choose fields on which to apply manure, the monetary value of cattle manure as perceived from a farmer's perspective, and how densely farmers choose to apply manure. Using response data from a mail-survey of farmers operating near feedlots, I found that a farmer's manure source, perceptions about manure application, and practical knowledge, along with some personal and farm-operation characteristics, are related to how farmers perceive manure's value, and to how efficiently they apply it. Having one's own livestock and viewing manure as an inexpensive fertilizer are factors that appear to increase manure's perceived value. Factors that reduce manure's perceived value include years of experience in farming, cover-crop nutrient crediting, size of an operation, and concern for the hazard of water pollution. Recognizing the nutrient value of applied manure to reduce the quantity of commercial fertilizer being applied could substantially increase a farm's profitability while protecting water resources from over-application of nutrients. Yet while farmers typically reduced the nitrogen application on a manured field, that reduction was usually small relative to the nutrients added. This concurs with the results of numerous other studies concluding that many farmers are deliberately over-fertilizing to seek the best possible yield and applying extra nitrogen to plan for the most favorable climatic conditions possible. While farmers might be expected to distribute manure more sparingly over a larger field, the opposite turned out to be true. This finding is consistent with the plausible hypothesis that larger fields are especially appealing as places to dispose of large amounts of manure. In addition to exploring some of the practical aspects of a farmer's role as a manure manager, I have found it relevant to consider some of the structural background elements that make it inevitable for most farmers to over-apply nitrogen as a means of maximizing yield when growing cattle-feed crops. Farmers' economic success depends in large part on complying with the recommendations of agricultural conglomerate companies that supply their inputs. Note that nitrogen is typically over-applied to corn crops even in areas where no manure is used or available. Being expected to over-apply nitrogen, farmers are unlikely to hold back on applying manure, and are likely to see only benefits in adding organic matter to the land they are cropping. The primary research presented here provides some dimensions in which to work with farmers, aiming toward curbing the over-application of crop nutrients.
Keywords: manure management; nutrient management; sustainable agriculture; natural resources; environmental sociology; pollution